GENERASI Z DI RUANG KELAS: TANTANGAN DAN PELUANG BARU DALAM MEREKRUT DAN MENGEMBANGKAN GURU MILENIAL - Khusnina, Kanzah; Aimah, Siti (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study is important because it reveals the role of millennial teachers as digital inspirators in integrating technology into learning at Madrasah Aliyah Negeri 2 Banyuwangi. The contribution of this study lies in providing insight into strategies, challenges, and best practices in using technology to improve the quality of education. The research method used is qualitative with a case study approach. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation studies. Interviews were conducted with 25 male and female informants. This study also discusses the importance of developing specific skills for millennial teachers in dealing with the characteristics of Generation Z which continue to develop dynamically in the classroom. The results show that the role of millennial teachers is not only limited to teaching, but also as agents of change who facilitate collaboration between generations, enrich students' learning experiences, and create a more inclusive and innovative learning environment. Opportunities and challenges for teachers as student inspirations include collaboration and mentoring between generations, balance of age and cross-generational relationships, and understanding the characteristics of Generation Z as challenges in learning